Corporate governance in family firms: The Norwegian maritime sector - Kristin Wallevik (Copenhagen Business School (CBS), 2009)
The four papers in this thesis investigate corporate governance in family firms from different angles, with emphasis on industry and industry networks. I divide the industry networks into social and commercial networks, where social networks are measured by interlocking boards and commercial networks by investments in other firms in the same industry. Focus is on the governance structures in family firms, how industry and networks may be determinants of family ownership, and the effect of family ownership and strong industry networks on financial performance in certain industries (such as the maritime industry). Two of the papers are theoretical papers and two are empirical papers. The empirical papers are based on the same hand-collected dataset comprising 167 Norwegian listed companies from 1996-2005. The first paper - “Corporate Governance in Family firms” comprises a survey of the corporate governance literature on family firms, paying attention to the unique issues in the governance of these firms. I discuss different forms of ownership and how different agency contexts and business environments may suit family ownership better than other ownership structures. I also discuss how firms can reap the benefits of family ownership, by using a relational governance model, if there is an atmosphere of positive relationships, trust and shared visions. A relational governance model focuses on the social capital embedded in personal relations between owners, managers and board members. A contractual governance model, however, focuses on finding the optimal incentives in the relations between owners and managers, in addition to having greater focus on the monitoring role of the board. These two models may complement and supplement each other in a governance structure. The question is how these different governance models affect firms' operations, decision-making, and competitiveness. The second paper - “The Effect of Industry Networks on Family Ownership” deals with possible effects of industry networks on the prevalence of family firms in different industries. I discuss how various networks can be determinants of family ownership, in addition to elements like incentives, monitoring, and altruism, as well as firm, industry and nation specific factors. I also discuss whether family firms can gain more from these industry networks than other firms due to a higher degree of ”thick trust”, strong owner-manager relations and the use of a relational governance structure. This paper proposes that strong social and commercial networks affect the number of family firms in an industry, as a result of the social capital embedded in these relations. Paper three - “Social and Commercial Networks as Determinants of Family Ownership - The Norwegian Shipping Industry” is an empirical paper testing whether industry networks are among the determinants of family ownership in the Norwegian shipping industry. The overall question is why family ownership is more prevalent in some industries, and which elements that influence this ownership structure. I focus on industry effects such as the number of firms in an industry and the social and commercial industry networks between firms. These are potential determinants of family ownership. I find that both industry and various industry networks have a significant and positive effect on family ownership in the shipping industry. The fourth paper - “Family Ownership, Networks and Financial Performance” takes up the question whether family ownership and various networks affect financial performance, measured by Tobin's q and ROA lagged, or not. Earlier studies come to different conclusions regarding the relationship between family ownership and firm performance, which may be due to differences in the agency context of the studies. I add industry and industry networks as central variables to disentangle some of the contextual factors in this relationship. This paper argues that it is not necessarily the family ownership that affects performance, but how this ownership is used in a strategic manner. Establishing and using networks are seemingly a means of operation in some industries, sometimes with a positive effect on performance.
hdl:10398/7901
Keywords: 650